Exercise of Varying Durations: No Acute Effects on Cognitive Performance in Adolescents - van den Berg, Vera; Saliasi, Emi; Jolles, Jelle; de Groot, Renate H. M.; Chinapaw, Mai J. M.; Singh, Amika S. (Frontiers in Neuroscience, 2018)
Participation in structured physical activity is assumed to have a positive effect on cognitive and academic performance. A single bout of moderate to vigorous exercise has been found to have a small acute positive effect on the cognitive performance of children and adolescents. However, the dose-response effects of exercise duration are largely unknown. Therefore, the current study examined the acute effects of moderate-to-vigorous exercise with a duration of either 10, 20, or 30 minutes on selective attention and working memory performance of young adolescents. One hundred and nineteen adolescents (11-14 years old) participated in a randomized, controlled crossover study. Adolescents were assigned to one of the three exercise durations, each paired with a sedentary control session of the same duration. Cognitive performance was measured before and immediately after the exercise and control condition. The Attention Network Test and n-back task were used to measure selective attention and working memory, respectively. There were no significant exercise effects on selective attention (i.e. alerting, orienting or executive control) or working memory performance. Furthermore, there were no differential effects of exercise duration. In sum, exercise bouts with a duration of 10, 20, or 30 minutes did not improve, but neither deteriorate cognitive performance of young adolescents compared to a sedentary control condition.